1993
DOI: 10.1002/gcc.2870080105
|View full text |Cite
|
Sign up to set email alerts
|

Tissue culture loss of aneuploid cells from carcinomas of the prostate

Abstract: The frequency of aneuploid cells in cultured prostate carcinoma specimens was investigated. Ploidy distribution of the original tissue was established by flow cytometry (FCM). Fluorescence in situ hybridization (FISH) of chromosome I was applied to directly isolated and cultured cells to investigate whether any modifications in the ploidy distribution of chromosome I took place during tissue culture. In six tumor specimens that were diploid by FCM and FISH, no differences were found in the ploidy distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 20 publications
4
16
0
Order By: Relevance
“…24 We have found a decrease in tumor progression in vitro for the HaCaT-ras model system and these findings are in agreement with reports demonstrating an in vitro selection against tumorigenic subpopulations in breast adenocarcinomas, 58 SCCs arising in Bowen' disease, 59 and prostate carcinomas. 60 Tumor progression in vivo is thought to be associated with specific genetic alterations and/or the selection of genetic subpopulations supposedly induced by adverse environmental conditions, eg, hypoxia. 61,62 Genetic analyses of our A-5/A-5RT cell progression model supports both mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…24 We have found a decrease in tumor progression in vitro for the HaCaT-ras model system and these findings are in agreement with reports demonstrating an in vitro selection against tumorigenic subpopulations in breast adenocarcinomas, 58 SCCs arising in Bowen' disease, 59 and prostate carcinomas. 60 Tumor progression in vivo is thought to be associated with specific genetic alterations and/or the selection of genetic subpopulations supposedly induced by adverse environmental conditions, eg, hypoxia. 61,62 Genetic analyses of our A-5/A-5RT cell progression model supports both mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this success, many groups are using variations of lowCa 2+ -SFD medium containing known growth factors [e.g., PrEBM complete medium or keratinocyte serum-free medium (K-SFM) complete medium from Invitrogen (Carlsbad, CA) in an attempt to grow sufficient numbers of prostate cancer cells from surgical material obtained at radical prostatectomy for molecular analysis and to establish new serially passageable prostate cancer cell lines (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Such a serum-free approach is favored because FCS contains a variety of undefined, and thus hard to standardize, factors in addition to its potent ability to stimulate growth to unwanted prostate stromal cells (i.e., fibroblasts and smooth muscle cells).…”
Section: +mentioning
confidence: 99%
“…+ loss) characteristic of the starting malignant cells obtained directly from the patient without culture (29,30), and (c) they usually are not tumorigenic when inoculated into nude mice (26,27,30). In contrast, all of the malignant prostate cancer cell lines established in high (i.e., >650 Amol/L)-Ca 2+ -FCS containing medium have karyotypic abnormalities, are spontaneously immortal (i.e., serially passageable), and are tumorigenic when inoculated into nude mice (18).…”
Section: +mentioning
confidence: 99%
“…Initial studies suggested that f75% of prostate cancer tumors had normal male karyotypes; however, there is now evidence by subsequent analysis over cell culture times that normal cells seem to be selected for in vitro (4,5); therefore, growth of tumor cells was not ideal. Several candidate chromosomes have been suggested as playing a role in the development of prostate cancer, among which are chromosomes 1,7,8,10,17, and X (6-10).…”
Section: Introductionmentioning
confidence: 99%